RELATION BETWEEN COMPLICATING FACTORS OF HYPOSPADIA AND COMPLICATIONS AFTER TIP: A RETROSPECTIVE STUDY - Aritonang, Johannes; Rodjani, Arry; Wahyudi, Irfan (Indonesian Journal of Urology, 2016)
Objective: This study aims to find an association between hypospadias complicating factor for complications that occurred after hypospadias reconstruction, focusing on tubularized incised plate (TIP) as reconstruction techniques are most commonly used. Material & methods: The study data was obtained from medical records of urologic hypospadias patients in Cipto Mangunkusumo General Hospital, Jakarta. Samples are those who underwent hypospadias reconstruction in Cipto Mangunkusumo General Hospital, since April 2002 until May 2014 with a total sampling method. Data were analyzed using SPSS ver 14. Results: We collected 127 patients who underwent the TIP technique with a mean patient age and treatment duration was 7.58 years and 10.95 days. Fistule is the most common complication in patients with post-TIP hypospadias accounting for as high as 32 (25.2%). Bivariate analysis showed a significant correlation between the location of the hypospadias meatus (distal) with torsion of the penis (n = 2; p 0.019). Conclusion: On the basis of the technical complications TIP, such as fistules, meatus stenosis, urethral stricture, torsion of the penis, and glans dehiscence, then the indication for TIP should be clear or selective.